Sosialisasi Spirit Kewirausahaan dan Peluang Usaha Bagi Jemaat GKP Rehoboth Jatinegara, Jakarta Timur - Nenny Anggraini; Juaniva Sidharta; Arya Gina Tarigan; Adolf Hutabarat; Maria Yulan Christina; Virgina Poppi Panjaitan; Flora Ferdinanda Imoliana; Carolina Florencia Sembiring (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Entrepreneurship is the process of creating, developing, and managing a business with the aim of generating profit, whether in the form of products, services, or innovations that can meet market needs. Entrepreneurship plays a significant role in economic, social, and community welfare development. The KPEJ program of GKP Rehoboth Jatinegara recognizes the importance of fostering the entrepreneurial spirit, especially by reviving positive initiatives that can motivate women to create home-based business opportunities as an alternative means to improve family income. This is especially important as the number of those interested in or already running a business has not shown a significant increase.Thus, the main issue arises: how can the spirit of entrepreneurship be enhanced through available business opportunities? This requires an understanding of how to socialize the entrepreneurial spirit, with the hope of encouraging the congregation’s enthusiasm for entrepreneurship by recognizing and taking advantage of existing opportunities. Therefore, there is a need for socialization efforts targeting the women of the GKP Rehoboth Jatinegara congregation, particularly to help them understand the importance of cultivating an entrepreneurial spirit and making good use of business opportunities.The implementation of this community service activity aims to provide outreach on the importance of developing an entrepreneurial spirit by utilizing business opportunities for the church congregation. It will be held onsite at GKP Rehoboth Jatinegara and is expected to have a positive impact by inspiring and encouraging women in the congregation to start their own businesses and improve their family's economic well-being